Government Debt in Emerging Market Countries : A New Data Set - Guscina, Anastasia (IMF Working Papers; Working Paper, 2006)
This paper presents a new database on government debt in 19 emerging market countries since 1980. The data set focuses on the structure of debt in terms of jurisdiction of insurance, maturity, currency composition and indexation. The paper presents stylized facts on debt structures and preliminary evidence on their determinants. We observe substantial crosscountry variation in the structure of domestic debt and find it to be associated with countries' record of monetary stability.